2021
DOI: 10.1590/acb360603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of S53P4 bioactive glass and low-level laser therapy on calvarial bone repair in rats submitted to zoledronic acid therapy

Abstract: To evaluate the influence of bioactive glass and photobiomodulation therapy (PBMT) in calvarial bone repair process in rats submitted to zoledronic acid therapy. Methods: Twenty-four rats were selected and treated with the dose of 0.035 mg/kg of zoledronic acid every two weeks, totalizing eight weeks, to induce osteonecrosis. After the drug therapy, surgical procedure was performed to create 5-mm diameter parietal bone defects in the calvarial region. The rats were then randomly assigned to groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…At 21 days, the β-TCP/S53P4 scaffolds induced greater bone formation in the defect area, presenting a significant difference (p < 0.05) when compared to β-TCP. Previous studies have proven the osteoconductive properties of this bioglass [78,79]. Signs of bone remodeling in defects filled with β-TCP scaffolds were observed in this study and agree with previous studies [7,8].…”
Section: Resultssupporting
confidence: 92%
“…At 21 days, the β-TCP/S53P4 scaffolds induced greater bone formation in the defect area, presenting a significant difference (p < 0.05) when compared to β-TCP. Previous studies have proven the osteoconductive properties of this bioglass [78,79]. Signs of bone remodeling in defects filled with β-TCP scaffolds were observed in this study and agree with previous studies [7,8].…”
Section: Resultssupporting
confidence: 92%
“…The bone defect is considered critical when it is not completely filled with bone tissue; in rat tibias, defects equal to or greater than 2 mm in diameter are considered critical 3 , 14 . Research carried out to evaluate the bone repair process in critical bone defects submitted to laser therapy associated with ZA is scarce in the literature 3 , 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is little research evaluating the association of zoledronic acid and laser therapy in the bone repair process 3 , alveolar 10 , and with biomaterials 11 . Additionally, none of the aforementioned studies evaluated the quality and quantity of collagen fibers, which are directly related to the bone repair process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies combined biomaterials with PBM and have achieved positive results in tissue regeneration [ 48–50 ]. However, some other studies showed that the superiority of PBM cannot be exploited when combined with biomaterials, which may be related to the excessive stimulation of tissue caused by the inappropriate dosage of biomaterials and PBM [ 51 ].…”
Section: Discussionmentioning
confidence: 99%